The effect of Using Social Media during formal working hours upon productivity from employee’s opinionThe Study applied on EBU’s employees in STC - Alharbi, Sanad Khulaif (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to identify the level of social media usage by the Saudi Communications Officer during the official working hours, and to identify the extent of the impact of the social media usage on the employee’s productivity. The study also aimed to determine the most important means to reduce this phenomenon, as well as to know whether there are statistically significant differences in the opinion of the respondents towards productivity, which are attributable to personal variables. This study relied on the descriptive survey approach, and the study population consisted of business-sector employees in Saudi Telecom Company in Riyadh. 150 questionnaires were randomly distributed to the study population, and 130 questionnaires valid for analysis were retrieved. The most important results are that 67.7% of the sample believe that staff productivity is not decreased after using social media, as well as that there are no statistically significant differences at the level of 0.05 or less on work productivity through the different variables except for the variable of the purpose of social media usage. The most important recommendations: Employees should be advised not to use social media during work, and the necessity to prepare awareness messages to be sent through the message center as well as the "fingerprint" system. Furthermore, seminars should be held to discuss the possibilities of achieving the optimal use of social media services during the official working hours to complete the company’s business and not the employee’s private business.